2018
DOI: 10.1097/wnr.0000000000000960
|View full text |Cite
|
Sign up to set email alerts
|

Feature binding in auditory modality requires attention as indexed by mismatch negativity and N2b in an active discrimination task

Abstract: Currently, there are two opposing views on feature binding in the auditory modality: according to behavioral studies, this process requires focused attention, whereas electrophysiological studies suggest that feature binding may be fully automatic and independent of attention. Here, we examined whether feature binding depends on higher-level attentional processes by manipulating the attentional focus. We used four auditory stimuli that differed in two features: pitch and location. Two rare deviants could be de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…1 b. VMMN was examined in an early (160–200 ms) and a late (260–300 ms) time window, while we applied a single time window (120–200 ms) on the acoustic MMN epochs. The time windows were defined on previous study results 60 , 61 , 63 .…”
Section: Methodsmentioning
confidence: 99%
“…1 b. VMMN was examined in an early (160–200 ms) and a late (260–300 ms) time window, while we applied a single time window (120–200 ms) on the acoustic MMN epochs. The time windows were defined on previous study results 60 , 61 , 63 .…”
Section: Methodsmentioning
confidence: 99%
“…When shearers are functional, the experienced operator will adjust the height of the drum according to the cutting sound to carry out the coal cutting. Physiological research has shown that to some extent, the human ear has the characteristics of localization and time-frequency decomposition [13,14]. Therefore, in various complicated environments, the human ear can accurately capture necessary acoustic signals.…”
Section: Introductionmentioning
confidence: 99%